Applied Informatics and Communication International Conference, ICAIC 2011, Xi$1 (Ban, China, August 20-21, 2011, Proceedings, Part II /s - Zeng, Dehuai; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
The five volume set CCIS 224-228 constitutes the refereed proceedings of the International conference on Applied Informatics and Communication, ICAIC 2011, held in Xi'an, China in August 2011. The 446 revised papers presented were carefully reviewed and selected from numerous submissions. The papers cover a broad range of topics in computer science and interdisciplinary applications including control, hardware and software systems, neural computing, wireless networks, information systems, and image processing.
Keywords: Computer science; Computer network architectures; Data structures (Computer science).; Information theory; Information systems; Computer vision; Computer Science; Information Systems and Communication Service; Computer Imaging, Vision, Pattern Recognition and Graphics; Computer Systems Organization and Communication Networks; Theory of Computation; Data Structures, Cryptology and Information Theory; Computer Appl. in Administrative Data Processing